2012
DOI: 10.1016/j.semarthrit.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Erythrocyte Sedimentation Rate and C-Reactive Protein for the Diagnosis of Giant Cell Arteritis

Abstract: Objectives 1) To evaluate the utility of erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) for the diagnosis of giant cell arteritis (GCA) 2) to determine the frequency of normal ESR and CRP at diagnosis of GCA. Methods All patients undergoing temporal artery biopsy (TAB) between 2000 and 2008 were identified. Only subjects with both ESR and CRP at the time of TAB were included. The medical records of all patients were reviewed. Results We included 764 patients (65% women), mean age 72.7 (±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
156
2
15

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(191 citation statements)
references
References 15 publications
11
156
2
15
Order By: Relevance
“…Mahr et al 15 reported a 15% histological evidence of TA in 1,520 patients. Kermani et al 16 also found 22% accuracy for pathological diagnosis in 1,106 patients. However, Suelves et al 17 presented 68.4% positive biopsy results in their study.…”
Section: Discussionmentioning
confidence: 94%
“…Mahr et al 15 reported a 15% histological evidence of TA in 1,520 patients. Kermani et al 16 also found 22% accuracy for pathological diagnosis in 1,106 patients. However, Suelves et al 17 presented 68.4% positive biopsy results in their study.…”
Section: Discussionmentioning
confidence: 94%
“…In both 'poppers maculopathy' and photic maculopathy, there is focal disruption of the IS-OS junction centred at the fovea. [1][2][3][4] Moreover, the size, shape, echogenicity, and temporal evolution of the SD-OCT lesions appear indistinguishable in the two conditions. Patients also present with the same symptoms (scotoma, reduced vision, and phosphenes) and have the same slit-lamp findings (a pale yellow foveal lesion).…”
Section: Sir Response To Grzybowski and Justynskamentioning
confidence: 92%
“…Unfortunately some papers referred to were not published at the time of writing. 3,4 The table provided by Dr Grzybowski and Justynska highlights some important articles, some of which were referenced in our original report 5 and others which were summarized by key articles referenced. 6,7,8 Dr Grzybowski and Justynska remark that typical features commonly associated with GCA were not presented in our case.…”
Section: Sir Response To Grzybowski and Justynskamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors' inadvertent omission of two recent articles evaluating laboratory predictors of a positive temporal artery biopsy is potentially misleading. 2,3 The study by Parikh et al 4 used a much lower cut-off for normal CRP of 5 mg/l, which may be the reason for the high sensitivity of CRP reported in their study. In the study by Walvick and Walvick, 2 a CRP cut-off of 5 mg/l yielded a sensitivity of 94.9%, which means that 5.1% had a falsely normal CRP (less than 5 mg/l).…”
mentioning
confidence: 89%